Search for a reliable model for bisphosphonate-related osteonecrosis of the jaw: establishment of a model in pigs and description of its histomorphometric characteristics - Mitsimponas, Konstantinos; Moest, T.; Iliopoulos, Christos; Rüger, Thomas; Müller, Christiane; Lutz, Rainer; Shakib, K.; Neukam, Friedrich Wilhelm; Schlegel, K. A. (British Journal of Oral and Maxillofacial Surgery, 2016)
The pathogenesis of bisphosphonate-related osteonecrosis of the jaw (BRONJ) remains unknown, and the development of a reliable experimental model would help to improve our understanding of it. We used 12 domestic pigs of which 6 made up the experimental group and were treated with zoledronate 4mg intravenously weekly for 5 weeks, while the control group (n=6) were given no drugs. On day 60 the right second maxillary and mandibular third molars were extracted. Thirty days later 3 animals in each group were killed; the rest were killed 90 days later. Histopathological specimens from the extraction sites were analysed for bone density, collagen architecture, density of osteons, and the amount of non-mineralised bone. Bone density, amount of non-mineralised bone, and density of osteons differed significantly between the 2 groups (p<0.001 in each case), but the chromatic pattern dictated by the collagen architecture did not. Our results correspond to the observations that have been made in patients with BRONJ, which means that the histomorphometric conditions seen in patients can be reproduced in this experimental setting.
EVALuna2:24425